Serum bile acid profiles are associated with heart failure with preserved ejection fraction in patients with metabolic dysfunction‐associated fatty liver disease: An exploratory study - Zhou, Xiao‐Dong; Xu, Cui‐Fang; Chen, Qin‐Fen; Shapiro, Michael D.; Lip, Gregory Y. H.; Chen, Li‐Li; Targher, Giovanni; Byrne, Christopher D.; Tian, Na; Xiao, Tie; Huang, Chen‐Xiao; Ni, Yan; et al. (Diabetes, obesity & metabolism, 2024)
Aim To analyse the association between serum bile acid (BA) profile and heart failure (HF) with preserved ejection fraction (HFpEF) in patients with metabolic dysfunction‐associated fatty liver disease (MAFLD). Methods We enrolled 163 individuals with biopsy‐proven MAFLD undergoing transthoracic echocardiography for any indication. HFpEF was defined as left ventricular ejection fraction >50% with at least one echocardiographic feature of HF (left ventricular diastolic dysfunction, abnormal left atrial size) and at least one HF sign or symptom. Serum levels of 38 BAs were analysed using ultra‐performance liquid chromatography coupled with tandem mass spectrometry. Results Among the 163 patients enrolled (mean age 47.0 ± 12.8 years, 39.3% female), 52 (31.9%) and 43 (26.4%) met the HFpEF and pre‐HFpEF criteria, and 38 serum BAs were detected. Serum ursodeoxycholic acid (UDCA) and hyocholic acid (HCA) species were lower in patients with HFpEF and achieved statistical significance after correction for multiple comparisons. Furthermore, decreases in glycoursodeoxycholic acid and tauroursodeoxycholic acid were associated with HF status. Conclusions In this exploratory study, specific UDCA and HCA species were associated with HFpEF status in adults with biopsy‐confirmed MAFLD.